In vitro anthelmintic effects of cysteine proteinases from plants against intestinal helminths of rodents - Stepek, Gillian; Lowe, Ann E.; Buttle, David J.; Duce, Ian R.; Behnke, Jerzy M. (Cambridge University Press, 2007)
Infections with gastrointestinal (GI) nematodes are amongst the most prevalent worldwide, especially in tropical climates. Control of these infections is primarily through treatment with anthelmintic drugs, but the rapid development of resistance to all the currently available classes of anthelmintic means that alternative treatments are urgently required. Cysteine proteinases from plants such as papaya, pineapple and fig are known to be substantially effective against three rodent GI nematodes, Heligmosomoides polygyrus, Trichuris muris and Protospirura muricola, both in vitro and in vivo. Here, based on in vitro motility assays and scanning electron microscopy, we extend these earlier reports, demonstrating the potency of this anthelmintic effect of plant cysteine proteinases against two GI helminths from different taxonomic groups – the canine hookworm, Ancylostoma ceylanicum, and the rodent cestode, Rodentolepis microstoma. In the case of hookworms, a mechanism of action targeting the surface layers of the cuticle indistinguishable from that reported earlier appears to be involved, and in the case of cestodes, the surface of the tegumental layers was also the principal location of damage. Hence, plant cysteine proteinases have a broad spectrum of activity against intestinal helminths (both nematodes and cestodes), a quality that reinforces their suitability for development as a muchneeded novel treatment against GI helminths of humans and livestock.